Penerapan Media Komik Sains untuk Meningkatkan Minat dan Hasil Belajar Siswa pada Konsep Gejala Pemanasan Global di SMA Negeri 10 Bandung - Cholisoh, Elly (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2021)
The purpose of this study was to increase students' interest and learning outcomes in the concept of global warming symptoms through the application of science comics.. This research method used classroom action research conducted in 2 cycles and carried out in SMA Negeri 10 Bandung by taking a sample of 30 students of class XI IPA. The instruments used in this study were questionnaires and tests. The data from the research results were obtained through the pre-test and post-test in the first cycle with an average of 64.93 and 66.83 with the incomplete category, while in the second cycle the average score for the pre-test was 74.37 and the post-test was 88.66 with the complete category. . The results of data analysis showed that learning outcomes increased, while the results of the student interest questionnaire showed 92.59% of students were very interested and 7.41% of students were interested. The collected data were also analyzed by calculating the N-gain and t-test resulting in the N-gain in Cycle I = 0.05 in the low category, while Ngain in the second cycle = 0.56 in the moderate category. The results of the t-test calculation show that t_hit = 9.69 while t_tab = 2.05 so that t_ (hit>) t_tab. Based on the research data, it can be concluded that science comics can increase students' interest and learning outcomes in the concept of global warming symptoms.